(untitled) (Orfeu, 2020)
Music bands concentrate a significant part of the musical documentation produced or accumulated in Brazil, especially between the last decades of the 19th century and the first half of the 20th. This work has as its theme the collection of the Music Band of the 10th Military Region, a group formed by military musicians from the Brazilian Army, based in the state of Ceará. The beginning of the activities of the association dates back to centuries, but throughout the 20th century, a lot of material was produced and preserved in its collection. In this investigation, the objective is to understand the origins of the musicographic documents, in order to trace geographical routes of the process of constitution of the collection. To this end, a Diplomatic Musical Analysis was undertaken in several sets of sources in the collection. The results point to composers and copyists still little known in the national panorama, as well as routes of circulation of the sources that include the cities of Manaus (AM), Ceará-Mirim (RN), Recife (PE) and Rio de Janeiro (RJ).